50.7k views
1 vote
For f(x) =4x-1 and g(x) = x2 - 5, find (f-g)(x)

User Anthropomo
by
5.4k points

2 Answers

3 votes
(4x -1)-(2x-5)
4x -1 -2x +5
2x +4
User Miketaylr
by
5.6k points
7 votes

Answer:

(f - g)(x) = -x² + 4x + 4

General Formulas and Concepts:

Pre-Algebra

  • Properties

Algebra I

  • Combining like terms
  • Function notation

Explanation:

Step 1: Define

f(x) = 4x - 1

g(x) = x² - 5

(f - g)(x) = f(x) - g(x)

Step 2: Find

  1. Substitute: (f - g)(x) = 4x - 1 - (x² - 5)
  2. Distribute: (f - g)(x) = 4x - 1 - x² + 5
  3. Combine like terms: (f - g)(x) = -x² + 4x + 4
User Gaurav Shah
by
5.4k points